2010
DOI: 10.1093/imammb/dqq023
|View full text |Cite
|
Sign up to set email alerts
|

Identifying therapeutic targets in a combined EGFR-TGF R signalling cascade using a multiscale agent-based cancer model

Abstract: Applying a previously developed non-small cell lung cancer model, we assess 'cross-scale' the therapeutic efficacy of targeting a variety of molecular components of the epidermal growth factor receptor (EGFR) signalling pathway. Simulation of therapeutic inhibition and amplification allows for the ranking of the implemented downstream EGFR signalling molecules according to their therapeutic values or indices. Analysis identifies mitogen-activated protein kinase and extracellular signal-regulated kinase as top … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…This framework was then used to explore a number of complex questions: the role of epidermal growth factor receptor (EGFR) density in tumor progression, 8 the influence of genetic instability in tumor heterogeneity, 152 the components that control the proliferation-to-migration switch for brain tumors, 151 and the role of EGF and TGF β signal integration in non-small cell lung cancer. 144 Macklin et al . used an ABM approach to investigate breast ductal carcinoma in situ (DCIS), 90 using patient-specific molecular and cellular measurements to calibrate their model.…”
Section: Multiscale Modeling Methods In Cancermentioning
confidence: 99%
“…This framework was then used to explore a number of complex questions: the role of epidermal growth factor receptor (EGFR) density in tumor progression, 8 the influence of genetic instability in tumor heterogeneity, 152 the components that control the proliferation-to-migration switch for brain tumors, 151 and the role of EGF and TGF β signal integration in non-small cell lung cancer. 144 Macklin et al . used an ABM approach to investigate breast ductal carcinoma in situ (DCIS), 90 using patient-specific molecular and cellular measurements to calibrate their model.…”
Section: Multiscale Modeling Methods In Cancermentioning
confidence: 99%
“…These signaling pathways mediate cell proliferation and migration and are involved in angiogenesis. The authors identified novel anti-angiogenic targets by performing a sensitivity study on the model parameters to determine how changes in the molecular signaling pathways influence two tumor outcomes: tumor cell number and the rate of tumor expansion [76]. The analysis predicted, for example, that inhibiting MEK activity by 0.5-fold is the optimal inhibition strategy, because it reduces the number of tumor cells and inhibits tumor expansion toward the nutrient source.…”
Section: Computational Models Of Anti-angiogenic Therapeuticsmentioning
confidence: 99%
“…In the ABM, tumor cells are represented as individual agents (Figure 2A) with both proliferative and migratory potentials determined by levels of PLC and bound EGFR (Figure 3). The proliferative and migratory nature of tumor cells leads to tumor growth and expansion 6,7,88 . These hybrid multi-scale ABMs of tumor growth have shown that increased EGF receptor density correlates with tumor expansion based on early phenotypic switching driven by TGF-α autocrine signaling 6,7,88 .…”
Section: Examples Of Hybrid Multi-scale Abmsmentioning
confidence: 99%